Impacts and Strategic Decision-Making Guidelines for Thai Exporters from the United States International Trade Tariff Policies - น้อยโสภา, สุณัฐวีย์; จันทรโพธิ์ศรี, อารีรัตน์; เพชรโสม, ณัฐวดี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to 1) study the impact of the United States international trade tariff policy on Thai exporters goods, and 2) examine the strategic decision-making approaches of Thai exporters to mitigate pressure from the United States' international trade tariff policy. This qualitative research employed document collection, data analysis, and a literature review. In-depth interviews with exporters of frozen food, frozen seafood, and consumer goods. The study also involved interviewing experts with experience in export businesses. The research findings show that the five key areas of impact and strategic decision-making are: 1) Marketing and strategic marketing decisions; 2) Production and strategic production decisions; 3) Transshipping and strategic decisions on origin verification processes; 4) Finance and international exchange rates and strategic decisions; and 5) trade confidence and strategic decisions. The findings from interviews with exporters and experts, consistent with relevant documents and research, conclude that the US has uncertain trade policies. This will hurt export businesses in both the short and long term. Marketing strategies will need to be developed for existing export markets and for expanding into new markets through free trade agreements. This includes improving production processes to reduce costs and increase efficiency, strictly adhering to rules of origin, planning to mitigate exchange rate risk, and building strong customer relationships to ensure long-term trade trust.